Smart Bio-Nanocoatings with Simple Post-Synthesis Reversible Adjustment - Mikhail Kryuchkov; Zhehui Wang; Jana Valnohova; Vladimir Savitsky; Mirza Karamehmedović; Marc Jobin; Vladimir L. Katanaev (Biomimetics)
Nanopatterning of signal-transmitting proteins is essential for cell physiology and drug delivery but faces challenges such as high cost, limited pattern variability, and non-biofriendly materials. Arthropods, particularly beetles (Coleoptera), offer a natural model for biomimetic nanopatterning due to their diverse corneal nanostructures. Using atomic force microscopy (AFM), we analyzed Coleoptera corneal nanocoatings and identified dimpled nanostructures that can transform into maze-like/nipple-like protrusions. Further analysis suggested that these modifications result from a temporary, self-assembled process influenced by surface adhesion. We identified cuticular protein 7 (CP7) as a key component of dimpled nanocoatings. Biophysical analysis revealed CP7’s unique self-assembly properties, allowing us to replicate its nanopatterning ability in vitro. Our findings demonstrate CP7’s potential for bioinspired nanocoatings and provide insights into the evolutionary mechanisms of nanostructure formation. This research paves the way for cost-effective, biomimetic nanopatterning strategies with applications in nanotechnology and biomedicine.